Effects of colchicine in adults with metabolic syndrome: A pilot randomized controlled trial. Issue 7 (2nd April 2019) - Demidowich, Andrew P.; Levine, Jordan A.; Onyekaba, Ginikanwa I.; Khan, Shahzaib M.; Chen, Kong Y.; Brady, Sheila M.; Broadney, Miranda M.; Yanovski, Jack A.
Abstract : Aim: To evaluate the efficacy and safety of colchicine for improving metabolic and inflammatory outcomes in people with obesity and metabolic syndrome (MetS). Materials and methods: Adults with obesity and MetS, but who did not have diabetes, were randomized to colchicine 0.6 mg or placebo capsules twice daily for 3 months. The primary outcome was change in insulin sensitivity (SI ) as estimated by insulin‐modified frequently sampled intravenous glucose tolerance tests. Secondary outcomes included changes in other metabolic variables and inflammatory markers. Results: Of 40 participants randomized (21 colchicine, 19 placebo), 37 completed the trial. Compared with placebo, colchicine significantly reduced C‐reactive protein ( P <0.005), erythrocyte sedimentation rate ( P <0.01), white blood cell count ( P <0.005), and absolute neutrophil count ( P <0.001). Change in SI was not significantly different between colchicine and placebo arms (difference: +0.21 × 10 −5 ; CI −1.70 to +2.13 × 10 −5 min −1 mU −1 mL; P = 0.82). However, changes in some secondary outcomes, including homeostatic model assessment of insulin resistance ( P = 0.0499), fasting insulin ( P = 0.07) and glucose effectiveness ( P = 0.08), suggested metabolic improvements in the colchicine versus placebo group. Adverse events were generally mild and similar in both groups. Conclusions: This pilot study found colchicine significantly improved obesity‐associated inflammatory variables and showed a good safety profile among adults with obesity and MetS who did not have diabetes. These results suggest a larger, adequately powered study should be conducted to determine whether colchicine improves insulin resistance and other measures of metabolic health in at‐risk individuals.